One image is worth more than a thousand words: producing an atlas of medical signs for teaching clinical and forensic toxicology - Ricardo Jorge Dinis-Oliveira (Oxford University Press, 2022)
Clinical and forensic toxicology are critically involved in the acquisition of basic skills to correctly suspect intoxication, collect biological and non-biological materials for toxicological analysis, comprehend the complexities inherent to laboratory activity, and understand the fundamentals of toxicokinetics and toxicodynamics that underlie the interpretation of results. This works presents a pedagogical innovation proposal for the teaching of clinical and forensic toxicology based on a compilation of more than 3 000 cases where the image was fulcra for suspicion. The experience in this article follows the model practiced in bachelors, masters, and PhD degrees, as well as in other continuing training courses, where we are teaching toxicology for more than 15 years. All these levels of education are considered fundamental to the sound development of this science. This approach aims also to offer strength to the intervention of the true toxicologist in all the toxicological phases, besides the classic analytical chemistry. Indeed, it is impossible to provide effective clinical and forensic toxicological interpretations without a proper and broad education, and not thinking exclusively in terms of laboratory techniques. In the future, it will be interesting to evaluate knowledge retention and to propose a database of videos of signs related to intoxications.KEY POINTSA pedagogical innovation proposal for the teaching of forensic and clinical toxicology is presented.A universal and never-ending atlas of phtotographs related to signs of intoxications have been compile.Offering to our students an integrated teaching of clinical and forensic toxicology is crucial since both are grounded in analogous toxicological principles and are mutually dependent.